Children of the changing South : accounts of growing up during and after integration - Dickson, Foster; Molina, David (McFarland & Company, Inc., Publishers, 2012)
"In this collection of memoirs, writers, teachers, scholars and historians recall growing up in the South from the late 1950s to the early 1990s, revealing how the region changed over time, as well as how a Southern childhood varied across time, race, gender, socio-economic status, and geography"--Resumé vydavatele
Keywords: 1950-1990; 1951-2000; děti -- Spojené státy americké (jižní oblast) -- 1951-2000; sociální změna -- Spojené státy americké (jižní oblast) -- 1951-2000; kultura a společnost -- Spojené státy americké (jižní oblast) -- 1951-2000; rasové vztahy -- Spojené státy americké (jižní oblast) -- 1951-2000; sociální dějiny -- Spojené státy americké (jižní oblast) -- 1951-2000; children -- United States, Southern -- 1951-2000; social change -- United States, Southern -- 1951-2000; culture and society -- United States, Southern -- 1951-2000; race relations -- United States, Southern -- 1951-2000; social history -- United States, Southern -- 1951-2000; Spojené státy americké (jižní oblast) -- společenské poměry -- 1951-2000; Spojené státy americké (jižní oblast) -- sociální poměry -- 1951-2000; United States, Southern -- social conditions -- 1951-2000; sborníky; paměti; miscellanea; memoirs